The Effectiveness of Cinnamon extract (Cinnamomum burmannii) to reducing ureum level in male Rattus norvegicus Unilateral Ureteral Obstruction (UUO) model - Evi Lusiana; Theodorus Theodorus; Nita Parisa; Fatmawati Fatmawati; M. Ivan Pratama (Sriwijaya Journal of Medicine, 2022)
Cinnamon extract's effectiveness as a renoprotective has not been previously investigated due to its widespread use in daily life, either as a cooking ingredient or as a herb. The aim of this study is to determine the effectiveness extract of cinnamon (Cinnamomum burmannii) as a renoprotective in lowering urea levels in the kidneys. An in vivo experimental study with a pre-post test and control group design was conducted at the Faculty of Medicine's Animal House and Biotechnology Laboratories. Male white rats (Rattus norvegicus) were used as the research subjects. Thirty rat were divided into five groups: negative control, positive control, cinnamon extract at 50 mg/kgBW, 100 mg/kgBW, and 200 mg/kgBW. The data were processed using SPSS 22.0. Cinnamon extract doses of 100 mg/kgBW and 200 mg/kgBW were the most effective in reducing urea levels and suspending the progression of the renal fibrosis process in Wistar male white rats with unilateral ureteral obstruction (UUO) model.